The Political Identity of Ulama in the 2014 Indonesian Presidential Election - Leni Winarni (Al-Jami'ah: Journal of Islamic Studies, 2014)
The Indonesian presidential election of 2014 was possibly the most exciting, lively, intriguing, emotional, and brutish in the history of presidential elections since reformation in 1998. This paper explores the relationship between the political identities of ulama and their political views in the 2014 Indonesian presidential election. It  argues that their political endorsement of presidential candidates is not based on interest but on their political identity. By using constructivist ideas about identity, ulama’s political identities are constantly changing and influenced by factors beyond identity. This idea also emphasizes that identity is created and subjective. Transformation of the political identities of ulama is a way of showing their existence in the period since Indonesian independence in 1945. This paper explores how the political identities expressed by ulama influenced voters in the recent presidential election. How did their political identity affect both the kinds of political measures they took and their support for one of the president candidates? Did the ulama play a substantial political role in election of President Joko Widodo, or were there other factors? Is their political identity the salient factor in their support for either Prabowo Subianto or Joko Widodo? [Pemilu presiden tahun 2014 memang sangat menarik, hidup, penuh emosi, bahkan penuh intrik, jika dibandingkan dengan sebelumnya sejak 1998. Paper ini meneliti hubungan politik identitas yang dibawa oleh ulama dan pandangan politiknya pada pemilihan presiden Indonesia tahun 2014. Paper ini menemukan bahwa pandangan mereka tentang calon presiden tidak sertamerta menyangkut kepentingan politik, tetapi lebih pada politik identitas. Politik identitas para ulama terus berubah dan dipengaruhi oleh banyak hal di luar identitas tersebut. Ini juga menegaskan bahwa identitas itu ciptaan dan sekaligus subjektif. Transformasi politik identitas para ulama merupakan cara mereka menampakkan keberadaannya, bahkan sejak masa kemerdekaan 1945. Paper ini meneliti politik identitas yang ditampakkan para ulama yang mempengaruhi para pemilih dalam pemilu presiden. Bagaimana politik identitas itu berpengaruh pada politik dan pilihan serta dukungan presiden? Apakah ulama memainkan sesuatu dalam proses terpilihnya Presiden Joko Widodo, atau adakah faktor lain? Apakah hanya identitas yang menjadi satu-satunya faktor  untuk mendukung Prabowo Subianto atau Joko Widodo?]